2020
DOI: 10.1177/2054358120966819
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Age and Kidney Failure in Adults With Category 4 Chronic Kidney Disease

Abstract: Background: In people with severe chronic kidney disease (CKD), there is an inverse relationship between age and kidney failure. If this relationship is the same at any age (linear), one effect (hazard ratio) will be sufficient for accurate risk prediction; if it is nonlinear, the effect will vary with age. Objective: To investigate the relationship between age and kidney failure in adults with category G4 chronic kidney disease (G4 CKD). Methods: We performed a population-based study using linked administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Age is one of the non-modifiable factors that play a role in the progression of CKI, especially in old age. 18 The study results are in line with previous studies that more CKD incidence is in elderly than younger people. 19,20 Decreased estimated glomerular filtration rate (eGFR) in older people is one of the risk factors for high CKI cases at that age.…”
Section: Discussionsupporting
confidence: 92%
“…Age is one of the non-modifiable factors that play a role in the progression of CKI, especially in old age. 18 The study results are in line with previous studies that more CKD incidence is in elderly than younger people. 19,20 Decreased estimated glomerular filtration rate (eGFR) in older people is one of the risk factors for high CKI cases at that age.…”
Section: Discussionsupporting
confidence: 92%
“…We developed and validated 2 models to predict kidney failure in adults with G4-CKD accounting for the competing risk of death. The risk of kidney failure varies in adults with severe CKD depending on age, sex, index eGFR, degree of albuminuria, and comorbidities . The 2 competing risk models we built with these predictors demonstrated excellent accuracy (defined as well-calibrated models with C index 0.8-0.9) for the entire risk range and prediction time.…”
Section: Discussionmentioning
confidence: 95%
“…The risk of kidney failure varies in adults with severe CKD depending on age, sex, index eGFR, degree of albuminuria, 3,4 and comorbidities. 5,31 The 2 competing risk models we built with these predictors demonstrated excellent accuracy (defined as well-calibrated models with C index 0.8-0.9) for the entire risk range and prediction time. The standard Cox regression, which does not account for the competing risk of death, provided similar performance during the first 2 years after onset of G4-CKD, but differences began to emerge thereafter, especially among people older than 65 years or with more comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…21 Wahsh HA showed that eGFR decreased with advancing age. 22 is research shows that smoking was associated with less severe CKD which contradicts with the previous researches which are stated following. A research conducted by Yacoub R et al showed that smoking was associated with progression of CKD.…”
Section: Figure-2: Neutrophil / Eosinophil Ratio In DI Erent Stages O...mentioning
confidence: 57%